Analisis Konten Edukatif Malaka Project di TikTok - Thommy, Thommy; Junaidi, Ahmad (Kiwari, 2025)
TikTok is one of the most popular social media platforms and has become an effective medium for sharing information, including educational content. Malaka Project, an Indonesia-based organization, utilizes TikTok to deliver education focused on social, cultural, and critical thinking issues targeted at Generation Z. This study aims to analyze the influence of Malaka Project's content on the critical thinking abilities of Generation Z in Jakarta. Using a quantitative approach, data was collected through questionnaires distributed to respondents from Generation Z. The results show that Malaka Project's educational content positively impacts the development of critical thinking skills in Generation Z. Simple narratives and engaging visuals are key elements of Malaka Project's content success. However, this study also identifies the need to enhance the interactive aspects of the content to improve audience understanding. This research highlights TikTok's potential as an innovative educational platform and provides recommendations for increasing the impact of educational content, particularly in supporting Generation Z to think critically in filtering and analyzing information in an increasingly complex digital era. TikTok merupakan salah satu platform media sosial yang paling populer dan telah menjadi wadah efektif untuk berbagi informasi, termasuk konten edukatif. Malaka Project, sebuah organisasi berbasis di Indonesia, menggunakan TikTok untuk menyampaikan edukasi berbasis isu sosial, budaya, dan pemikiran kritis yang ditujukan kepada Generasi Z. Penelitian ini bertujuan untuk menganalisis pengaruh konten Malaka Project terhadap kemampuan berpikir kritis Generasi Z di Jakarta. Dengan pendekatan kuantitatif, data dikumpulkan melalui kuesioner yang disebarkan kepada responden dari kelompok Generasi Z. Hasil penelitian menunjukkan bahwa konten edukatif Malaka Project memiliki pengaruh positif terhadap pengembangan kemampuan berpikir kritis Generasi Z. Narasi yang sederhana dan visual yang menarik menjadi elemen kunci keberhasilan konten dari Malaka Project. Namun, penelitian ini juga menemukan perlunya pengembangan aspek interaktif dalam konten untuk meningkatkan pemahaman audiens. Penelitian ini menyoroti potensi TikTok sebagai platform edukasi yang inovatif dan memberikan rekomendasi untuk meningkatkan dampak konten edukatif, khususnya dalam mendukung Generasi Z untuk lebih kritis dalam menyaring dan menganalisis informasi di era digital yang semakin kompleks.